Nodular melanoma: five consecutive cases in a general practice with polarized and non-polarized dermatoscopy and dermatopathology - Cliff Rosendahl; Matthew Hishon; Alan Cameron; Sarah Barksdale; David Weedon; Harald Kittler (Mattioli1885, 2014)
Background: The incidence of nodular melanoma (NM) has been consistently described as at least 10-15% of total melanomas for over 15 years despite advances in diagnostic algorithms and medical technology. NMs are strongly correlated with faster rates of growth and poorer prognosis and thus provide clinicians with a challenge for early recognition. Objective: To evaluate diagnostic clues of consecutive histopathologically proven NMs in one general practice with particular emphasis on dermatoscopic characteristics and compare this to the published literature. Method: A retrospective observational study was performed of five consecutive histologically proven NM, from a total of 212 consecutive melanomas from a general practice in Brisbane, Queensland, Australia. Dermatoscopic images, both polarized and non-polarized, which appears to be a unique resource, and dermatopathologic slides were available for all lesions. Results: All of the NMs in this series were pigmented although one was hypomelanotic. Two of them were symmetrical. The most highly sensitive clues to NM were gray or blue structures and polarizing-specific white lines. Limitations: Due to the small number of NMs in this report no statistical significance can be attributed to the observational findings. Conclusion: This small series supports what is already known: that a significant proportion of NMs may be dermatoscopically symmetrical but that known clues to melanoma are frequently present.Nodular lesions, pigmented or non-pigmented, should be excised to exclude NM if there is any clue to malignancy, regardless of symmetry, unless a confident specific benign diagnosis can be made.